Hydrolytic Mechanism of a Metalloenzyme Is Modified by the Nature of the Coordinated Metal Ion - Zeyad H. Nafaee; Bálint Hajdu; Éva Hunyadi-Gulyás; Béla Gyurcsik (Molecules, 2023)
The nuclease domain of colicin E7 cleaves double-strand DNA non-specifically. Zn2+ ion was shown to be coordinated by the purified NColE7 as its native metal ion. Here, we study the structural and catalytic aspects of the interaction with Ni2+, Cu2+ and Cd2+ non-endogenous metal ions and the consequences of their competition with Zn2+ ions, using circular dichroism spectroscopy and intact protein mass spectrometry. An R447G mutant exerting decreased activity allowed for the detection of nuclease action against pUC119 plasmid DNA via agarose gel electrophoresis in the presence of comparable metal ion concentrations. It was shown that all of the added metal ions could bind to the apoprotein, resulting in a minor secondary structure change, but drastically shifting the charge distribution of the protein. Zn2+ ions could not be replaced by Ni2+, Cu2+ and Cd2+. The nuclease activity of the Ni2+-bound enzyme was extremely high in comparison with the other metal-bound forms, and could not be inhibited by the excess of Ni2+ ions. At the same time, this activity was significantly decreased in the presence of equivalent Zn2+, independent of the order of addition of each component of the mixture. We concluded that the Ni2+ ions promoted the DNA cleavage of the enzyme through a more efficient mechanism than the native Zn2+ ions, as they directly generate the nucleophilic OH− ion.